2016
DOI: 10.1021/jacs.5b12124
|View full text |Cite
|
Sign up to set email alerts
|

Solution Synthesis Approach to Colloidal Cesium Lead Halide Perovskite Nanoplatelets with Monolayer-Level Thickness Control

Abstract: We report a colloidal synthesis approach to CsPbBr3 nanoplatelets (NPLs). The nucleation and growth of the platelets, which takes place at room temperature, is triggered by the injection of acetone in a mixture of precursors that would remain unreactive otherwise. The low growth temperature enables the control of the plate thickness, which can be precisely tuned from 3 to 5 monolayers. The strong two-dimensional confinement of the carriers at such small vertical sizes is responsible for a narrow PL, strong exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
926
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 801 publications
(1,008 citation statements)
references
References 48 publications
61
926
2
6
Order By: Relevance
“…They showed that the thickness of CsPbBr 3 nanoplatelets can be tuned from 1 to 5 unit cells thick by changing the reaction temperature, with the monolayer platelets emitting at 400 nm (Figure 6e), whereas the bulk-like crystals emitted at 520 nm (Figure 6d). Similarly, Manna and colleagues 65 have shown that the thickness of CsPbBr 3 platelets could be precisely tuned between 3 and 5 monolayers, keeping a narrow emission and a strong blue shift of the PL peak compared with that of bulk CsPbBr 3 . In addition, they have also shown that the lateral size of the quantum-confined CsPbBr 3 nanoplatelets (thickness~3 nm) can be controlled up to the micrometer range by varying the ratio of shorter ligands (octanoic acid and octylamine) to longer ligands (oleic acid and oleylamine), while maintaining their thickness and, to a large degree, the optical properties.…”
Section: Quantum Confinement In Perovskite Ncsmentioning
confidence: 83%
See 1 more Smart Citation
“…They showed that the thickness of CsPbBr 3 nanoplatelets can be tuned from 1 to 5 unit cells thick by changing the reaction temperature, with the monolayer platelets emitting at 400 nm (Figure 6e), whereas the bulk-like crystals emitted at 520 nm (Figure 6d). Similarly, Manna and colleagues 65 have shown that the thickness of CsPbBr 3 platelets could be precisely tuned between 3 and 5 monolayers, keeping a narrow emission and a strong blue shift of the PL peak compared with that of bulk CsPbBr 3 . In addition, they have also shown that the lateral size of the quantum-confined CsPbBr 3 nanoplatelets (thickness~3 nm) can be controlled up to the micrometer range by varying the ratio of shorter ligands (octanoic acid and octylamine) to longer ligands (oleic acid and oleylamine), while maintaining their thickness and, to a large degree, the optical properties.…”
Section: Quantum Confinement In Perovskite Ncsmentioning
confidence: 83%
“…In a recent report Li et al 64 Figure 5 showed that CsPbX 3 NCs can be synthesized at room temperature, similar to the LARP method used for the MAPbX 3 system. Manna and colleagues 65 have demonstrated the synthesis of quantum-confined CsPbBr 3 nanoplatelets at room temperature. They have shown that anisotropic growth leads to the formation of nanoplatelets at room temperature through the injection of acetone in a mixture of precursor.…”
Section: (Figures 4f-h) the Initially Formed Cubic Ncs Transformed Intomentioning
confidence: 99%
“…To date, all-inorganic cesium lead halide perovskite have generated considerable attention because of their higher stability and outstanding optoelectronic properties comparable to the hybrid organic-inorganic perovskites [17][18][19][20]. Thus, a large number of CsPbX 3 (X = I, Br, Cl) perovskite nanostructures such as nanocrystals [21], nanowires [22], microsheets [23,24], nanocubes, were prepared by solution processing approach. Furthermore, the physical properties of all-inorganic nanocrystals could be adjusted by their geometric shape and size [25].…”
Section: Introductionmentioning
confidence: 99%
“…We further cross-checked that the method used to make the thin film conductive and photoconductive is not limited to this particular halide content. In particular, we demonstrated that the method can be applied to other shapes, including nanocubes (0D objects) and nanoplatelets 28 (2D objects, NPL) (see Figure S9), and to other Br:I ratios (see Figure S10). The typical responsivity of the film spans from 200 µA.W -1 to 1 mA.W -1 depending on the incident power.…”
mentioning
confidence: 99%